Utilization of Research Findings and their Role in Research Management as an Interdisciplinary Field - Mas'ud Kabiri (Interdisciplinary Studies in the Humanities, 2009)
Research management has been brought up as an interdisciplinary subject –a combination of “management” and “research methodology”- especially in Humaninties and Social Sciences research. As an essential concept in research management, utilization of research findings is so important that some believe neglecting it would cause failure of research efforts. Utilization Model is the frame within which the matter is programmed. Introducing different Utilization models, the present study attempts to suggest a variety of research frameworks to be selected in proportion to organizational status. Points of strength and weakness of any model have been explored here. Three different uses –instrumental, conceptual, and procedural- have been explained according to their corresponding utilization models. In the procedural use, various models are introduced including communication models, science push, knowledge driven, problem solving, demand push, diffusion, stetler, the knowledge-to action process, cronbach Rossi model in conceptual use, and the Ottawa model, Canadian Institutes of health research, understanding user context framework, collaborative model, and the utilization forced model for evaluation. They are introduced to be selected for different organizational structures. The variety of utilization models show that they are especially rooted in the local environment, and thus when applying them, the user should pay attention to the specific characteristics of the models besides the organizational and environmental specifications.